THE EFFECTS OF CHILDHOOD TRAUMA TOWARD DISSOCIATION IN THE NOVEL LIFE OF PI BY YANN MARTEL - Ramadhan, Syahrul; Prautomo, Adi (Prologue: Journal on Language and Literature, 2025)
This study poses two research questions. What form of childhood trauma is present in Yann Martel's novel Life of Pi? How did childhood trauma affect dissociation in the novel Life of Pi by Yann Martel? The researcher employs a qualitative method, presenting the problem in a descriptive manner. The researchers gathered primary data from the novel Life of Pi, which they then analyzed and interpreted. In the final results of this study, the scientists found five types of trauma with 35 data points: Loss, Sadness, and Disappointment. The researchers discovered three types of dissociation: structural dissociations, secondary dissociations, and complex dissociations. These findings reveal a complex relationship between many types of trauma and dissociation reactions. Research demonstrates that childhood trauma significantly impacts the protagonist's psychological state, leading to various forms of dissociation that impact his perception of reality and identity. This study finds the result of the research are childhood trauma of loss affect strongly the structural dissociation and sadness of childhood trauma strongly affects secondary structural dissociation and the last disappointment dominantly complex dissociation. It conlude that childhood trauma affects seriously dissociation.